Police Violence in Health Care Settings in US Media Coverage - Saadi, Altaf; Ray, Victor E. (JAMA network open, 2023)
Hospitals do not collect or share data tracking their policing and security activities despite their reliance on police and security personnel, including armed officers. Thus, little is known about how hospital security is associated with patient and staff safety. To examine the harms exerted by health care-affiliated police and security personnel. For this qualitative study, data were collected using a systematic Media Cloud search for US news media coverage from January 2011 to May 2022. A total of 18 987 articles on policing and hospitals were screened and a content and thematic analysis of articles that met the search criteria was conducted, which involved incidents that revealed harm to patients, patients' families, and staff. Data were analyzed from October 2022 to April 2023. Incident year, incident location (hospital name, city, state), survivor and victim characteristics (race and ethnicity, presence of mental illness), and a narrative description of the incident focusing on outcomes of harm exerted by police and security personnel in the health care setting. A total of 48 unique stories across 25 US states were included. The median (range) year published was 2017 (2009-2022). Harms reported to have been perpetuated by health care-affiliated police and security personnel were identified within 5 domains from 48 unique incidents: (1) patients shot by police or security personnel (17 patients); (2) patients subject to excessive use of force (17 patients); (3) patients arrested (7 patients); (4) patients subject to sexual assault (2 patients); and (5) hospital personnel or those considered collateral damage shot, injured, or arrested (5 individuals). Most survivors and victims were Black, although the race and/or ethnicity of involved individuals was not routinely reported across the news stories. Mental illness was the most documented medical condition among patients injured or killed by health care-affiliated police and security personnel. This qualitative study of US news media found that police and security personnel in hospitals were reported to have perpetuated harm via excessive force, sexual assaults, injuring patients and health care workers, and fatal shootings. Compounded by a lack of transparency and accountability mechanisms, this may represent an underrecognized manifestation of structural racism at the organizational level. Policy suggestions include introducing accountability measures, deescalation techniques, and removing arms from hospital security personnel to reduce harm and fulfill health care's healing mission.